MENGAKAR KARYA ILMIAH (Menulis Skripsi Kualitatif, Kuantitatif, dan Penelitian & Pengembangan) - Pohan, Jusrin Efendi (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2016)
This liretarue study intends to discuss related issues to the strength sand weaknesses of qualitative and quantitative method. That the method has productive potential for fostening the development of humanities the ories as well as methodology in the context to Indonesian world.